Equity valuation of CTT – Correios de Portugal, S.A. - Afonso, David Alexandre da Silva Machado (2015)
This dissertation provides a valuation of CTT’s equity. The literature review presented and the empirical evidence found concerning the usage of models in equity valuation, allowed choosing the DCF approach to make the valuation. The sum of the parts of the business in which the company is inserted – Mail, Business Solutions, Express & Parcels and Financial Services – yielded a price target of €9.15 for the YE15, which represents a potential upside of 17%. A “BUY” recommendation was given. Most multiples, in the relative valuation conducted, showed that CTT would trade above its peers. Lastly, a comparison with the most recent equity note from the biggest Portuguese private bank was made. All in all, the capitalization of the growth prospects in the Financial Services and countering the downing the structural decline of the Mail business were identified as the key factors that support the positive investment case of CTT.